Managing incontinence - Breitenmoser, Kurt.; Scoglio, Stephen; Garner, Simon; Hilakari, Jennifer; Video Education Australasia ([Bendigo, Vic.] : VEA, 2008)
'Urinary and faecal incontinence can be one of the most stigmatising and embarrassing disabilities to afflict both men and women in society today. The cost to the individual can be measured in loss of confidence, embarrassment, social isolation, relationship stress and breakdown; not just in laundering and costs of continence products. However there is hope for individuals afflicted with incontinence. New therapies, products and appliances, and building design can all assist the individual. This program examines management strategies to assist individuals and their carers to maintain dignity and independence. Presented by continence expert Jennifer Hilakari, it includes clear explanations of types of incontinence (stress urge, functional, overflows and enuresis, and faecal) and strategies to assist.' - product description.
Introduction -- An introduction to incontinence -- Types of incontinence: stress/urge -- Types of incontinence: functional -- Types of incontinence: overflows and enuresis -- Types of incontinence: faecal -- Strategies to assist -- Conclusion.
Includes web links.
Producer/director: Kurt Breitenmoser ; writer: Stephen Scoglio ; exeuctive producer: Simon Garner
Hosted by Jennifer Hilakari.
DVD
Keywords: Urinary incontinence -- Popular works; Fecal incontinence -- Popular works; Urinary stress incontinence -- Popular works